Data from: Water use by Swedish boreal forests in a changing climate - Hasper, Thomas B.; Wallin, Göran; Lamba, Shubhangi; Hall, Marianne; Jaramillo, Fernando; Laudon, Hjalmar; Linder, Sune; Medhurst, Jane L.; Räntfors, Mats; Sigurdsson, Bjarni D.; Uddling, Johan (Dryad, 2016)
The rising levels of atmospheric carbon dioxide concentration ([CO2]) and temperature have the potential to substantially affect the terrestrial water and energy balance by altering the stomatal conductance and transpiration of trees. Many models assume decreases in stomatal conductance and plant water use under rising [CO2], which has been used as a plausible explanation for the positive global trend in river run-off over the past century. Plant water use is, however, also affected by changes in temperature, precipitation and land use, and there is yet no consensus about the contribution of different drivers to temporal trends of evapotranspiration (ET) and river run-off. In this study, we assessed water-use responses to climate change by using both long-term monitoring and experimental data in Swedish boreal forests. Historical trends and patterns in ET of large-scale boreal landscapes were determined using climate and run-off data from the past 50 years, while explicit tree water-use responses to elevated [CO2] and/or air temperature were examined in a whole-tree chamber experiment using mature Norway spruce (Picea abies (L.) Karst.) trees. The results demonstrated that ET estimated from water budgets at the catchment scale increased by 18% over the past 50 years while run-off did not significantly change. The increase in ET was related to increasing precipitation and a steady increase in forest standing biomass over time. The whole-tree chamber experiment showed that Norway spruce trees did not save water under elevated [CO2] and that experimentally elevated air temperature did not increase transpiration as decreased stomatal conductance cancelled the effect of higher vapour pressure deficit in warmed air. Our findings have important implications for projections of future water use of European boreal coniferous forests, indicating that changes in precipitation and standing biomass are more important than the effects of elevated [CO2] or temperature on transpiration rates. Hasper et al. 2015 - All ...